Scenario simulation of land use change and carbon storage response in Henan Province, China: 1990–2050 - Liyao Fan; Tianyi Cai; Qian Wen; Jing Han; Shuxue Wang; Junhao Wang; Chaohui Yin (Ecological Indicators, 2023)
The carbon storage service of terrestrial ecosystems has an veritable impact on the global carbon cycle and, in turn, on global climate change. Hence, both assessing and predicting the impact of land use changes on carbon storage are necessary to reduce carbon emissions and mitigate climate change. Therefore, using integrated valuation of ecosystem services and tradeoffs (InVEST) model with remote sensing data, this study systematically analyzes the land use/cover change (LUCC) and the carbon storage response characteristics of land types in Henan Province, China in the 1990–2020 period. The study also uses patch-generating land use simulation (PLUS) model to predict the LUCC and carbon storage in Henan Province from 2023 to 2050 under different scenarios, including Business as Usual (BAU), Ecological Conservation (EC), and Urban Development (UD) scenarios. The following results are noted: (1) The LUCC mainly comprises the conversion of farmland to construction land. Presently, Henan Province’s carbon storage is found to have decreased by 339.72 Tg due to LUCC, which is characterized as “high in the west and low in the east.” (2) Regarding the three aforementioned scenarios, the province’s construction land is predicted to increase to its greatest extent under the UD scenario. Under the EC scenario, its woodland and farmland areas will be effectively protected. Therefore, the highest level of carbon reserves will likely be found in the EC scenario, followed by that in the BAU scenario, while the lowest level of carbon reserves should be seen in the UD scenario. The carbon reserves of Henan Province in 2050 will be 312.07 Tg, 233.43 Tg, and 394.49 Tg lower than that in 2020 under the BAU, EC, and UD scenarios, respectively. In sum, this study provides the scientific basis of the decisions aimed at the facilitation of low-carbon development, the optimal utilization of land spaces, and the development of an ecological civilization in Henan Province.